THE DEVELOPMENT OF ROLE-PLAYING LEARNING MODEL DESIGN ON ACCOUNTING SUBJECT - Laurentius Saptono; Natalina Premastuti Brataningrum (Jurnal Kependidikan, 2019)
THE DEVELOPMENT OF ROLE-PLAYING LEARNING MODEL DESIGN ON ACCOUNTING SUBJECTAbstractThis study was aimed to generate a product of an effective role-playing learning model design on basic competences of practicing accounting cycles in service companies for the eleventh grade students. The research procedures were done based on ADDIE model. The developed product design was validated by the experts of learning materials, the experts of learning media, the experts of learning design, and the experts of characters building. The product was tested on Stella Duce 1 Senior High School students both in small groups which consisted of 12 people and a large group of 40 people. The instruments which was used to assess product validity included material aspects, media aspects, aspects of learning, and aspects of character building. The result of the experts’ validation and testing to students showed that it was a very good developed product. This meant that the role-playing learning model design on basic competences of practicing accounting cycles in service companies for the eleventh grade students was worth implementing in the learning activities.PENGEMBANGAN DESAIN PEMBELAJARAN MODEL ROLE-PLAYING PADA MATA PELAJARAN AKUNTANSIAbstrakPenelitian ini bertujuan untuk menghasilkan produk berupa desain pembelajaran model role-playing yang efektif untuk pembelajaran pada kompetensi dasar mempraktikkan siklus akuntansi perusahaan jasa untuk siswa kelas XI SMA. Prosedur pengembangan produk penelitian dilakukan berdasarkan Model ADDIE. Produk yang dikembangkan divalidasi oleh ahli materi pembelajaran, ahli media pembelajaran, ahli desain pembelajaran, dan ahli pendidikan karakter. Produk diujicobakan kepada siswa-siswa SMA Stella Duce 1 baik kelompok kecil yang terdiri dari 12 orang maupun kelompok besar yang terdiri dari 40 orang. Instrumen untuk menilai validitas produk mencakup aspek materi, aspek media, aspek pembelajaran, dan aspek pendidikan karakter. Hasil validasi dari para ahli dan hasil ujicoba pada siswa-siswa menunjukkan bahwa produk yang dikembangkan dinyatakan sangat baik. Artinya, desain model role-playing yang dikembangkan untuk pembelajaran pada kompetensi dasar mempraktikkan siklus akuntansi perusahaan jasa untuk siswa kelas XI SMA layak untuk diimplementasikan dalam praktik pembelajaran.